PENILAIAN POTENSI PENGEMBANGAN PARIWISATA YANG BERKELANJUTAN PADA KAWASAN PARIWISATA PANTAI BATAKAN DI KABUPATEN TANAH LAUT - Sukarti Sukarti; Moehansyah Moehansyah; Enny Dwi Pujawati; M. Adriani (EnviroScienteae, 2011)
The tourism potential of Batakan Beach Resort, which is the slope coast with the bed of brownish white sand along ±12 km, is the special attraction for the visitors. Batakan beach is the area of Animal Conservation in Pelaihari Tanah Laut. Its function is converted to Natural Tourism Park on the basis of Keputusan Menteri Kehutanan Nomor 695/Kpts-II/1991. The assessment is required to find out the potentials of the development as the sustainable tourism resort. The objective of the research was to study the development potentials of the tourism resort of Batakan beach. The assessments were on the land suitability, the supporting factors of the beach tourism resort, and the plan for increasing the potential of the sustainable development of the resort. The land suitability assessment included: the suitability with Rencana Tata Ruang Wilayah (RTRW), the area width and the level of the physical suitability of the beach. The assessment of the supporting factors included: the recreation, health, shopping, entertainment, accommodation, and infrastructure facilities, the public acceptance and the government policy. The research was descriptive and applied the analysis survey method. The result of the research indicated that the assessment of the land suitability received total score 471,1. It indicated that the tourism resort of Batakan beach was at the first rank with the total score 742,46. The Batakan beach was very reliable to develop as the sustainable tourism resort although there were some supporting factors receiving lower score namely the health, shopping, entertainment, and infrastructure facilities.